- #1

iamalexalright

- 164

- 0

[tex]H = \frac{-\hbar^2}{2m}\frac{\delta^{2}}{\delta x^{2}} + V(x)[/tex]

[tex]p = -i\hbar \frac{\delta}{\delta x}[/tex]

[tex][H,p] =[/tex]

[tex] Hp - pH =[/tex]

[tex]\frac{-\hbar^2}{2m}\frac{\delta^{2}}{\delta x^{2}} * -i\hbar \frac{\delta}{\delta x} + V(x)-i\hbar \frac{\delta}{\delta x} - -i\hbar \frac{\delta}{\delta x}\frac{-\hbar^2}{2m}\frac{\delta^{2}}{\delta x^{2}} - -i\hbar \frac{\delta}{\delta x}V(x) = [/tex]

[tex]i\frac{\hbar^{3}}{2m}\frac{\delta^{3}}{\delta x^{3}} - V(x)ih\frac{\delta}{\delta x} - i\frac{\hbar^{3}}{2m}\frac{\delta^{3}}{\delta x^{3}} + i\hbar \frac{\delta}{\delta x}V(x) = [/tex]

[tex]i\hbar \frac{\delta}{\delta x}V(x) - V(x)ih\frac{\delta}{\delta x}[/tex]

Given [tex]\Delta A \Delta B \geq |<C>|/2[/tex] with [tex]|<C>| = [A,B][/tex], find

[tex]\Delta A \Delta B[/tex]

[tex]<C> = \int \Psi^{*}(i\hbar \frac{\delta}{\delta x}V(x) - V(x)ih\frac{\delta}{\delta x})\Psi dx[/tex]

Can I go from there? Is any of this correct?